ESG and Firm Value: The Moderating Role of Stock Returns and EPS - R, Mandasari; DEWINDA, Mutty Claudia (Journal of Governance, Taxation and Auditing, 2025)
This study examines the influence of Environmental, Social, and Governance (ESG) on firm value, and explores the role of stock returns and Earnings Per Share (EPS) as moderating variables. Using secondary data from 84 public companies listed on the Indonesia Stock Exchange from 2020 to 2023, this study applies a panel regression approach with a fixed effects model. The analysis results indicate that ESG has a negative and significant influence on firm value. Furthermore, the interaction between ESG and stock returns also shows a significant negative effect, indicating that high stock returns can amplify the negative impact of ESG on firm value. Conversely, the interaction between ESG and EPS does not show a significant effect, indicating that EPS does not act as a moderator in this relationship. This finding has an important implication that ESG implementation does not automatically increase firm value. This occurs because ESG initiatives need to be supported by appropriate management strategies and effective communication with investors.